A Project Report on Mobile Multimedia Administrator Tool - RAMYA V and RASHMI A (2006)
INTERNAL GUIDE: VIJETH S ANATI, MVJCE EXTERNAL GUIDE: SHANKAR, PACIFIC IT SOLUTION
Keywords: Mobile Multimedia Administrator Tool